Nursing care with an intercultural approach to pregnant women in primary care health centers. - Leon Yosa, Joanna (2023)
The objective of this essay is to reflect on nursing care with an intercultural approach to pregnant women, in primary care health centers. An exploratory documentary study was carried out for the development of this essay. Women who live in rural areas are very vulnerable, especially during pregnancy, a topic of interest in public health due to the records of mortality, obstetric violence and human rights, among other particularities. These women have access to primary care services where nursing with a humanistic profile must adapt their care to interculturality, so that they can comply with their prenatal check-ups. However, there is evidence that demonstrates the problems within the gestational stage that can worsen depending on certain factors such as age, customs, beliefs, access to the health system and the absence of prenatal control. That is why interculturality in nursing is relevant and important in prenatal care because it allows a comprehensive analysis of pregnant women, taking into account sociocultural aspects, beliefs, traditions, and even relationships with the environment, their family and midwives. that can influence pregnancy care.